Decadal-scale onset and termination of Antarctic ice-mass loss during the last deglaciation - Weber, Michael E.; Golledge, Nicholas R.; Fogwill, Chris J.; Turney, Chris S. M.; Thomas, Zoë A. (Nature communications, 2021)
Emerging ice-sheet modeling suggests once initiated, retreat of the Antarctic Ice Sheet (AIS) can continue for centuries. Unfortunately, the short observational record cannot resolve the tipping points, rate of change, and timescale of responses. Iceberg-rafted debris data from Iceberg Alley identify eight retreat phases after the Last Glacial Maximum that each destabilized the AIS within a decade, contributing to global sea-level rise for centuries to a millennium, which subsequently re-stabilized equally rapidly. This dynamic response of the AIS is supported by (i) a West Antarctic blue ice record of ice-elevation drawdown >600 m during three such retreat events related to globally recognized deglacial meltwater pulses, (ii) step-wise retreat up to 400 km across the Ross Sea shelf, (iii) independent ice sheet modeling, and (iv) tipping point analysis. Our findings are consistent with a growing body of evidence suggesting the recent acceleration of AIS mass loss may mark the beginning of a prolonged period of ice sheet retreat and substantial global sea level rise. It may have taken only a decade to repeatedly destabilize the Antarctic Ice Sheet after the last Ice Age as shown by a new data-model study. The ice sheet lost ice for centuries each time before it abruptly re-stabilized again.